High School Students Awareness and Attitudes Toward Climate Change - Ayu Deshiana; Ida Sriyanti; Ismet Ismet (Berkala Ilmiah Pendidikan Fisika, 2022)
Climate change is a tremendous threat to the environment and human beings. Students are among the younger generation who immediately feel the effects of climate change. The younger generation is expected to have the knowledge and a positive attitude toward the framework for climate change adaptation and mitigation. The objectives of this study describe awareness and attitudes concerning climate change held by 611 high school students in South Sumatra. The methods of this study employed qualitative research. The findings of this research indicated that 98.4% of students were aware of climate change. Additionally, more than 80% of students know climate change contributes to droughts, floods, declining water quality, and the spread of vector-borne illnesses such as dengue fever and malaria. 95.7 % of students have a positive attitude toward mitigating climate change.